General electronic community / Yan Pei Sun - Yan , Pei Sun (2005)
This project Generic electronic community system has been proposed for facilitate the real life community environment in more effective way which comprised of some modules such as forum, message board, file sharing, photo gallery, testimonial, announcement and etc. People are able to gather in a “cyber space” to conduct discussion or interaction via internet. A complete literature review and analysis on existing e community system have been done to gain more valuable information and knowledge about this project. Methodology and techniques used in the researches and developing system has discussed with emphasis on the chosen waterfall model with prototyping. Microsoft Internet Information Services, SQL Server, ASP.NET and Microsoft visual Studio.Net have been chosen as development tools and software tools. Functional and non-functional requirement, hardware and software requirements of the project have been listed down in the project. Much consideration have also been taken on the system design of the proposed system which include architecture design. Network design, process design database design and user interface design.